Perceived effects of education among female members of the Ata Manobo, Mandaya and Mansaka communities in the Davao Region - Jorolan, Genevieve T. (Banwa, 2005)
The Davao Region in Southern Mindanao is rich in IP culture whose unique characteristics have prompted the conduct of several researches. For the purposes of this study, three IP communities of lumad groups were chosen: the Ata Manobo of Talaingod, Davao del Norte; the Mandaya of Sangab, Caraga, Davao Oriental; and the Mansaka of Maragusan, Compostela Valley. The study aims to find out how the female members of the three lumad groups view education and its impact on their respective cultures. The role of the female lumad has been defined by the communities' deeply rooted traditions.They play a vital role for the survival of the indigenous communities. Their attitude towards the kind of education introduced to them by the Philippine educational system, and their views on its impact on their cultural traditions, are essential for the insights that designers and planners of the educational curricula in all levels of education can derive from the data.